Compiling data for food composition data bases (United Nations Univ. Press, 1991)
This book offers methods for analysing foods, the organization and content of food composition tables and data bases, and procedures for the accurate international interchange of data-focuses specifically on the issues involved gathering, and estimating where necessary, the data for such tables and data bases